2012
DOI: 10.1021/ja302506t
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Enzymatic Galactosylation of N-Acetylglucosaminolipids in Lipid Microdomains

Abstract: A fluoro-tagged N-acetylglucosamine-capped glycolipid that can form lipid microdomains in fluid phospholipid bilayers has been shown to be enzymatically galactosylated by bovine β(1,4)-galactosyltransferase. MALDI MS, HPLC, and LC-MS revealed that the rate of enzymatic transformation was significantly enhanced by lipid clustering; at a 1% mol/mol loading, clustered glycolipids were galactosylated 9-fold faster than glycolipids dispersed across the bilayer surface. The transformation of the GlcNAc "glycocalyx" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 61 publications
0
49
0
Order By: Relevance
“…1 This has demonstrated that the multivalent presentation of a particular glycotope on an appropriate scaffold (i.e. [2][3][4][5][6][7][8][9][10][11][12][13] Indeed, the promise that specic lectin-mediated processes (i.e., pathogen recognition, viral entry, tumor migration and metastasis events, etc.) can affect signicantly its potency and selectivity of binding with a given target protein, relative to that of a monovalent counterpart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This has demonstrated that the multivalent presentation of a particular glycotope on an appropriate scaffold (i.e. [2][3][4][5][6][7][8][9][10][11][12][13] Indeed, the promise that specic lectin-mediated processes (i.e., pathogen recognition, viral entry, tumor migration and metastasis events, etc.) can affect signicantly its potency and selectivity of binding with a given target protein, relative to that of a monovalent counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…cellmembrane, dendrimer, polymer, nanoparticle, etc.) [8][9][10][11]13,[15][16][17][43][44][45][46] Glycosidases constitute a large and important family of enzymes that are responsible for assuring the proper biosynthesis and/or biodegradation of glycoproteins, glycolipids and also proteoglycansthe very entities that serve as ligands for complimentary lectins in vivo. [2][3][4][5][6][7][8][9][10][11][12][13] Indeed, the promise that specic lectin-mediated processes (i.e., pathogen recognition, viral entry, tumor migration and metastasis events, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Webb and co‐workers have developed models of “lipid rafts”, which are liquid‐ordered microdomains within the phospholipid bilayer, concentrating cell‐adhesion molecules (Figure 1). 4 GlcNAc sugars were covalently attached to perfluoroalkyl–pyrene motifs, which were previously shown to form vesicle aggregates with significant phase separation 5. These ordered fluorolipid domains within the membranes mimicked the naturally occurring “lipid raft” at cell membranes.…”
Section: Modulation Of Enzyme Activity With Polyvalent Substratesmentioning
confidence: 98%
“…[9,10] Given the complexity of carbohydrate structure and the need for highly selective transformations, carbohydrate-basedt arget libraries are an excellent test for the application of biocatalysis to synthesis of DNA-encoded ligand libraries. [15][16][17][18][19] The overall strategy to accessalibrary of DNA-carbohydrate glycoconjugates by using ac ombination of chemical methods and biocatalysis is outlined in Scheme1.T he initial step involvesc hemical ligation of the first carbohydrate building block,f ollowed by biocatalytic transformationt oe ither elongate the glycan structure by glycosylationo rg enerate an aldehyde by oxidation of the primary sugar hydroxyl groupsf or the site-specific modification of the carbohydrate by reductive amination or hydrazone ligation. [12] Given the lack of precedent, we decided to study biocatalysts that had previously been shown to tolerate diverse conjugates and focus on glycosylationr eactions catalyzed by glycosyltransferases [13] and selectivef unctionalization of carbohydrates.…”
mentioning
confidence: 99%
“…Moreover, the reductivea mination approach was generally associated with both high conversiona nd purity when using av ast variety of amine derivatives, makingt his reactions uitablef or DEL synthesis. In contrast, high conversion was obtained for secondary amines 48-51 (Table S2, entries [13][14][15][16], particularly with pyrrolidine 48 (95 %, entry 13). [31] Briefly,t he aldehyde in MOPS buffer (300 mm, pH 7.4) was mixed with al arge excesso fa mine and sodium cyanoborohydride (NaBH 3 CN), followed by incubation for 16 h at 37 8C.…”
mentioning
confidence: 99%